Xavier Le Roy e l’identità corporea come prodotto delle circostanze - Rossetti, Tobia (Mimesis Journal, 2022)
The paper addresses the performance Product of Circumstances (1999) by Xavier Le Roy, highlighting the particular corporeality that it conveys, promotes and theorizes. The work of the French choreographer is approached from an epistemological perspective and related to the “constructivist” corporeal episteme promoted by a part of contemporary dance. In conclusion, the article questions how revolutionary or not are the premises of Le Roy’s non-dance compared to the production system of contemporary dance.